The Development of Inquiry Based Integrated Science Modules on The Structure and Function of Plant Tissues Integrated with Religious Values For Class VIII Secondary School - Kholis, Noor; Rohmadi, Mukhlis; Septiana, Nurul (Journal of Biology Education, 2024)
The purpose of this research is to create an Inquiry-based integrated science module that focuses on the structure and function of plant tissues while incorporating religious values to help students learn in grade VIII SMP/MTs. This module is designed to improve students' understanding of science concepts and religious values in the context of Islamic education. This study was conducted at MTs Islamiyah, Palangka Raya City, from 30 April - 30 June academic year 2023-2024. R&D (Research and Development) was used, which is a 4-D development model consisting of Definition, Design, Development, and Distribution. The results of the study showed that the developed module can be used The validation results of the material experts obtained an average of 3.78, which is very valid, the design experts obtained 3.71, and the religious value experts obtained 3.45, which is very valid, and the students' responses to the module obtained an average of 3.76, which is very valid, and the teacher's response was 3.62. The module test results were 3.49 for individual test, 3.59 for small group test, and 3.67 for field test, respectively.